Reading habits of UNIMAS Lecturers - Sarini, Binti Marty (Universiti Malaysia Sarawak (UNIMAS), 2008)
This study aims to investigate reading habits for work related and pleasure of lecturers in UNIMAS. The objectives of the study is to find out frequency on reading for work related and pleasure in a week, time spent on academic reading materials for work related in a week, time spent on non academic reading materials for pleasure in a week, types of reading materials and purposes of reading and lastly factors affecting reading frequency and time spent for work related and pleasure in a week. The participants of the study are 348 lecturers from eight faculties and Centre for Language Studies. Questionnaires were used to collect data and data were analyzed by using frequency and percentages. Results from this study revealed that most lecturers have high rate reading for work related compared to pleasure in a week. There is no difference on time spent for either academic reading for work related or non academic reading for pleasure in a week, as lecturers spent 1-4 hours for both types of reading. Apparently, most lecturers read various types of materials such as journal, course related materials, academic book, internet (website), newspaper and magazine for educational, informative purposes and for pleasure. Finally, the findings revealed that most lecturers perceived lack of time due to (work, family, and commitment) as the important factors affecting frequency of reading and time spent on reading for work related and pleasure in a week. Generally, lectures have positive attitude towards reading for work related but they have to impartial reading for pleasure in a week as well, nevertheless, lack of time (work, family, and commitment) is the important factors which affect frequency of reading and time spent on reading for work related and pleasure in a week.